الربط بين الموجودات الصدوية والنتائج السريرية والمخبرية في متلازمة المبيض متعدد الكيسات. - العباس, باسل; سلمان, ربا; سلوم, نعمى (Latakia University Journal -Medical Sciences Series, 2019)
PCOS is considered as the most common endocrine disoreder in young women. As ultrasound examination of such cases is cheap, available, and non invasive, it is commonly used in patients with suspected PCOS. The study aimed to determine the role of transabdomen ultrasound examination in diognosis PCOS comparing to clinical and biological presentations. 115 patients with one or more clinical symptoms of PCOS were enrolled in the study. Laboratory examination and transabdomen ultrasound was done for studying ovarian volume and morphology. The average age of women with PCOS was 23,12±4,3. Hirsutism was the most common clinical feature and had been noticed in 90 patients and formed 78,3%. The most common ultrasonographic feature was found is increasing the small follicles more than 12 follicle of(2-9) mm in diameter and was noticed in 85 patients(37,9)% for the right ovary and in 78 patients(67,8)% for the left ovary, and most of these follicles had a peripheral distribution giving tha apperance of string of pearls.The biological features (high levels of total testosterone) had been found in 98 patients and formed 85,21%. The compatibility between biological results and diagnosed ultrasounal features had been noticed in 93 patients(80,86)% وصفت هذه المتلازمة لاول مرة عام 1935 من قبل العالمين Stein و Leventhal و تعرّف بأنها إصابة مزمنة يحدث فيها تكرار الدورات اللاإباضية مصحوبا بفرط الهرمونات الذكرية (الاندروجينات). كان هدف البحث تحديد دور التصوير بالأمواج فوق الصوتية عبر البطن كإجراء غير راض في تشخيص متلازمة المبيض متعدد الكيسات و المقارنة مع الموجودات السريرية و المخبرية. تمّ قبول 115 مريضة في دراستنا من مراجعات مشفى تشرين الجامعي خلال الفترة الممتدة من (3/6/2018 و لغاية 3/6/2019) ممن يشتكين واحداً أو أكثر من أعراض المبيض متعدد الكيسات. تم إجراء التحاليل الهرمونيّة المناسبة, حيث اعتمدنا هنا بشكل أساسي على قيم التستسترون الكلي في الدّم, كما تمّ فحص المريضات بواسطة جهاز الإيكوغرافي عبر البطن لدراسة المبيضين من حيث الحجم, عدد الجريبات و توزعها, صدويّة اللحمة. تراوحت أعمار مرضى عينة الدراسة بين 16و 38سنة، ,وسطيا 23.12±4.5 سنة, كانت الشعرانية هي العرض السريري الأكثر شيوعاً حيث شوهدت لدى (90 مريضة بنسبة 78.3%). لوحظ في دراستنا ان اهم المظاهر الصدوية المشاهدة كانت زيادة عدد الجريبات اكثر من 12 جريب بقطر لا يتجاوز (2-9) ملم في المبيض حيث لوحظت لدى (85 مريضة بنسبة 73.9%للمبيض الأيمن و 78 مريضة بنسبة 67.8%للمبيض الأيسر) مع الاشارة للتوزع المحيطي الغالب لهذه الجريبات معطية مظهر عقد اللؤلؤ. بلغ عدد المريضات اللواتي اظهرن إيجابية الفحص الهرموني (التستسترون الكلي في المصل ) 98 مريضة بنسبة 85.21% وتوافقت نتائج الفحص الهرموني مع المظاهر الصدوية المشخصة عند 93 مريضة بنسبة 80.86%.